Dive In : Exploring Our Connection With The Ocean - Anne Erickson (Victoria, Canada Orca Book Publishers,Canada, 2018)
We're all connected to the ocean, and the ocean to us. The ocean provides half the oxygen we breathe; it feeds us, creates our weather and provides us with water. But we haven't been as kind to the ocean in return. The problems are many: pollution, overfishing, rising seas and acid waters. What can be done? Don't despair; take action. Dive In! explores our intimate connection with the ocean and provides every reader with an achievable set of actions that can help improve ocean health for our sake and the sake of the millions of marine plants and animals that share the planet with us. Filled with colorful photos and positive stories, Dive In! is as informative as it is inspirational.
Keywords: Life on Land; Global Issues -- Global Issues; Environment Issues -- Environment Issues